APPLICATION OF TPACK TECHNOLOGY IN TEACHING THE SCIENCE OF “COMPUTER ANIMATION” (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2023)
The development of professional competencies in teaching students how to create computer animation, the use of an e-learning system in teaching computer animation requires a new approach from the future computer science teacher. This article highlights the implementation of these approaches in teaching students the subject of "Computer Animation" based on TPACK technology.